2013
DOI: 10.1002/gbc.20055
|View full text |Cite
|
Sign up to set email alerts
|

Future Arctic Ocean primary productivity from CMIP5 simulations: Uncertain outcome, but consistent mechanisms

Abstract: [1] Net Arctic Ocean primary production (PP) is expected to increase over this century, due to less perennial sea ice and more available light, but could decrease depending on changes in nitrate (NO 3 ) supply. Here Coupled Model Intercomparison Project Phase 5 simulations performed with 11 Earth System Models are analyzed in terms of PP, surface NO 3 , and sea ice coverage over 1900-2100. Whereas the mean model simulates reasonably well Arctic-integrated PP (511 TgC/yr, 1998(511 TgC/yr, -2005 and projects a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
216
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 192 publications
(225 citation statements)
references
References 77 publications
(103 reference statements)
4
216
0
1
Order By: Relevance
“…Five BOGCMs manifested similar levels of light limitation owing to a general agreement on the simulated sea ice distribution [Popova et al 2012]. On the other hand, the ESMs participating in the Vancoppenolle et al [2013] study showed that Arctic phytoplankton growth was more limited by light related to sea ice than by nutrient availability for the period of 1980-1999. Furthermore, with the large uncertainties on present-day nitrate in the sea ice zone, ESMs used in the framework of the CMIP5 exercise were inconsistent in their future projections of primary production and oligotrophic condition in the Arctic Ocean [Vancoppenolle et al, 2013].…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Five BOGCMs manifested similar levels of light limitation owing to a general agreement on the simulated sea ice distribution [Popova et al 2012]. On the other hand, the ESMs participating in the Vancoppenolle et al [2013] study showed that Arctic phytoplankton growth was more limited by light related to sea ice than by nutrient availability for the period of 1980-1999. Furthermore, with the large uncertainties on present-day nitrate in the sea ice zone, ESMs used in the framework of the CMIP5 exercise were inconsistent in their future projections of primary production and oligotrophic condition in the Arctic Ocean [Vancoppenolle et al, 2013].…”
Section: Discussionmentioning
confidence: 59%
“…This observation is not necessarily new [Popova et al, 2012;Vancoppenolle et al, 2013], but one should be cautious when interpreting this result because these three simulated parameters were positively biased (i.e., means usually overestimated) (Figures 8 and 9). For example, the simulated, mean surface NO 3 was vastly overestimated, especially in the lowproductivity, nutrient-depleted interior regions of the Arctic Ocean, i.e., the Beaufort Sea and the central Arctic Basin where model and in situ iNPP agreed best (Figures 6b and 6e; Table 4).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In this region, future trends in primary production are critically dependent on the relative importance of different environmental drivers: beneficial effects of increased irradiances and potentially detrimental effects of decreased nutrient input, provided that the effects of enhanced stratification dominate over those of increased wind-driven mixing (Arrigo and van Dijken 2011;Vancoppenolle et al 2013;Ardyna et al 2014;Tremblay et al 2015). Observational data are indispensable to estimate the potential effects of climate change on Arctic phytoplankton assemblages.…”
Section: Introductionmentioning
confidence: 99%
“…In typical Arctic ecosystems the most important primary consumers are large-sized herbivorous copepods, which have lifecycles synchronized with the seasonal algae bloom (Kosobokova, 2012). Among the key questions is what would be the joint effect of Arctic warming, ocean freshening, pollution load and acidification on the Arctic Ocean ecosystem (Janout et al, 2016), primary production (Vancoppenolle et al, 2013;Arrigo and van Dijken, 2015) 15 and carbon cycle (Christensen et al, 2017). Considering the Arctic marginal seas, however, high volumes of additional GPP seem highly unlikely.…”
Section: Arctic Marine Ecosystemsmentioning
confidence: 99%